Drip irrigation and black polyethylene mulch pressure on development, yield and water-use efficacy of tomato (International Journal of Irrigation and Water Management, 2014)
A two year field study was conducted during 2001-2002 and 2002-2003 on sandy loam soil to investigate the effect of drip irrigation and black polyethylene mulch compared with surface irrigation, on growth, yield, water-use efficiency and economics of tomato (Lycopersicon esculentum Miller). Drip irrigation at 80% evapo-transpiration (ET) crop based on pan evaporation applied gave significantly higher fruit yield (45.57 tonnes/ha) compared with the surface irrigation (29.43 tonnes/ha). Use of black polyethylene mulch plus drip irrigation further raised the fruit yield to 57.87 tonnes/ha. Plant height, leaf area index, dry matter production, fruit weight and yield increased significantly with the use of drip irrigation alone and in conjunction with polyethylene mulch compared to surface irrigation alone or with mulch. Water-use efficiency under drip irrigation alone, drip irrigation with polyethylene mulch and surface irrigation was 0.97, 1.23 and 0.42 tonne/ha-cm, respectively. Among different irrigation levels, drip irrigation at 80% ET resulted in higher net returns (34431 Rs/ha) and benefit cost ratio (1.76) in tomato. However, maximum net returns (51386 Rs/ha) and benefit cost ratio (2.03) was found with drip irrigation at 80% ET coupled with polyethylene mulch compared to other treatments. Drip irrigation besides giving a saving of 38% water resulted into 55% higher fruit yield compared to surface irrigation.